A COMMUNITY STUDY DRUG ABUSE AND ADDICTION IN BASRA GOVERNORATE, CAUSES AND PROPOSALS TO REDUCE THEM: A FIELD STUDY ON A SAMPLE OF CONVICTS - Abdul Hassan Rahim Hammadi (Scholar Express Journals, 2023)
The research aims to shed light on the biggest scourge threatening the community of Al-Basra City. This scourge is the drugs. They are spreading in Basra City , In addition, the research will shed light on the groups that use and deal in drugs in the City . The study included a sample consisting of males and females who live in the City in order to identify the reasons push them to use the drug and the details surrounding this problem . The targeted groups were divided on the basis of age, marital status, educational level and type of housing and its negative effects. The study concluded that: Bad friends and economic reasons were the main reasons behind this problem.
Keywords: drugs; abuse; addiction; crystal